Prevalence and Progression of Stage 0 Macular Hole in Fellow Eyes of Patients with Idiopathic Full-thickness Macular Hole - Chun, Ji Woong; Kim, Chang Hwan; Kim, Ju Young; Oh, Hyun Sub; Kim, Soon Hyun; Kwon, Oh Woong; You, Yong Sung (Korean journal of ophthalmology, 2021)
To assess the prevalence and progression of a stage 0 macular hole in the fellow eye of patients with an idiopathic full-thickness macular hole. The fellow eyes of 189 patients who underwent idiopathic full-thickness macular hole surgery were examined by biomicroscopy and spectral domain-optical coherence tomography (SD-OCT). A subset of 21 fellow eyes with a stage 0 macular hole was observed. Changes in the macular hole were evaluated by biomicroscopy and SD-OCT for an average of 29 months. Among the 21 eyes, 15 showed no change in perifoveal vitreous detachment (71.4%). Two eyes (9.5%) developed complete vitreofoveal separation, and one of the two developed a separation after progression to stage 1A. Among 21 eyes, 5 (23.8%) developed above stage 1A, and one of the five progressed to stage 1B after five years, which was successfully treated with vitrectomy and gas tamponade. Perifoveal vitreous detachment in the fellow eye on SD-OCT, defined as a stage 0 macular hole, occurred at an earlier phase than stage 1A macular holes and may progress to an advanced stage. Therefore, patients who undergo macular hole surgery and have a stage 0 macular hole or perifoveal vitreous detachment in the fellow eye should be followed closely.